Handbook of research on industrial informatics and manufacturing intelligence innovations and solutions - Khan, Mohammad Ayoub, 1980-; Ansari, Abdul Quaiyum, 1962-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"As industrial systems become more widespread, they are quickly becoming network-enabled, and their behavior is becoming more complex and intelligent. The Handbook of Research on Industrial Informatics and Manufacturing Intelligence: Innovations and Solutions is the best source for the most current, relevant, cutting-edge research in the field of industrial informatics. The book focuses on different methodologies of information technologies to enhance industrial fabrication, intelligence, and manufacturing processes. Industrial informatics uses the infrastructure of information technology for analysis, effectiveness, reliability, higher efficiency, security enhancement in the industrial environment, and this book collects the latest publications relevant to academics and practitioners alike"--Provided by publisher.
1. Fundamentals of industrial informatics and communication technologies / Abdul Quaiyum Ansari, Mohammad Ayoub Khan -- 2. Industrial information security, safety, and trust / Ashraf Darwish ... [et al.] -- 3. Fuzzy logic: concepts, system design, and applications to industrial informatics / Siddhartha Bhattacharyya, Paramartha Dutta -- 4. ANNs for identifying shock loads in continuously operated biofilters: application to biological waste gas treatment / Eldon R. Rene ... [et al.] -- 5. Novel meta-heuristic optimization techniques for solving fuzzy programming problems / Pandian Vasant -- 6. Functional safety of distributed embedded control systems / Mohamed Khalgui ... [et al.] -- 7. Integration of fuzzy logic techniques into DSS for profitability quantification in a manufacturing environment / Pandian Vasant, Irraivan Elamvazuthi, Timothy Ganesan -- 8. Rough set based aggregation for effective evaluation of Web search systems / Rashid Ali, M. M. Sufyan Beg -- 9. Technology support for knowledge management in industrial settings: issues and implications / Zaigham Mahmood ... [et al.] -- 10. Industrial informatics: assertion of knowledge from raw industrial data / Iram Shahzadi, Qanita Ahmad, Imran Sarwar -- 11. Adaptive network based fuzzy interference system (ANFIS) modeling of an anaerobic wastewater treatment process / Eldon R. Rene ... [et al.] -- 12. Evolutionary computing: principles and applications to portfolio optimization / Siddhartha Bhattacharyya, Paramartha Dutta, Paramita Bhattacharya -- 13. Widespread adoption of RFID technology / Nova Ahmed -- 14. Application of wireless sensor networks in industrial settings / P C Jain -- 15. Linux based real-time control over industrial networks / Peter Fodrek ... [et al.] -- 16. Traffic control of two parallel stations using the optimal dynamic assignment policy / Seifedine Kadry -- 17. Feasible automatic reconfigurations of real-time OS tasks / Mohamed Khalgui ... [et al.] -- 18. Improving industrial product lifecycle management by semantic data federations / Matthias Wauer ... [et al.] -- 19. SoftPLC-based control: a comparison between commercial and open-source EtherCAT technologies / Stefano Scanzio -- 20. Performance evaluation of a dynamic model of a photovoltaic module for real-time maximum power tracking / M. S. Alam, A. T. Alouani -- 21. III-V nitride based novel solid-state terahertz power-source: application in defense and industry / Moumita Mukherjee -- 22. Secure RFID-enablement in modern companies: a case study of the pharmaceutical industry / Matthieu-P. Schapranow ... [et al.] -- 23. An intelligent hybrid model for bus load forecasting in electrical short-term operation tasks / Ricardo Menezes Salgado, Takaaki Ohishi, Rosangela Ballini -- 24. Intelligent techniques for the analysis of power quality data in electrical power distribution system / Zahir Javed Paracha, Akhtar Kalam.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed March 20, 2012).
Keywords: Industrial electronics; Production engineering -- Data processing; Computer integrated manufacturing systems; Automation; Intelligent agents; Machine learning; Adaptive learning; Neuro-psychoanalytic models; Neural network; Data fusion; Platform technologies; Human computer interaction; Mechatronics and robotics; Electronic books